INVESTIGATING LANGUAGE SHIFTING TOWARDS STUDENTS BATCH XII OF SMKN PENERBANGAN ACEH: A CASE STUDY - Aulia, Rizki; Mulyani, Mulyani; Suryani, Suryani (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
Language shifting is a phenomenon in sociolinguistics study that occurs as a result of language contact. Language shifting concerns usage issues language by a group of speakers that can occur due to transfer from one speech community to another. This research was conducted towards students Batch XII SMKN Penerbangan Aceh. This study was a case study employing a descriptive qualitative approach. This research aims to investigate the language used by the students at the living environment and school /dormitory. The data collection used an online questionnaire. After the data was collected, further the data were analyzed based on the steps used, starting from tabulating, identifying, counting, displaying, verifying, and then describing based on the problem aspects of the study discussed. Regarding the research results, the students who come from various regions and have their local language, when they are in the SMKN Penerbangan Aceh, use Bahasa because of some factors: teacher, education staff, diversity of origins, and the other people in SMKN Penerbangan Aceh environment.